Handbook of UV degradation and stabilization - Wypych, George (ChemTec Publishing, 2015)
In this text, George Wypych provides a comprehensive reference guide to help those working with plastics to limit this damage and deterioration through the use of UV stabilizers. The author begins with physics of radiation energy, transmission, and absorption and their effect on materials.